(untitled) (Bangladesh Journal of Urology, 2020)
We report a case in which a 14 years old boy with feeling of heaviness of Left testis and also dragging discomfort on the same side with gynecomastia both sides. Ultrasonography showed heterogenous mixed echogenic mass lesion in left hemi scrotum-possibly Germ cell tumor either teratoma or seminoma. His hormonal status was within normal limit except Estradiol which was 150pg/ml. The mass removed by inguinal approach and histopathology confirmed the benign large cell calcifying Sertoli cell tumour (LCCSCT). The detection of LCCSCTs may indicate to an underlying genetic multiple neoplasia syndrome such as PJS or CNC. Surgery is rarely indicated and aromatase inhibitors constitute an effective treatment for those cases that are associated with gynecomastia and/or advanced skeletal age1. Bangladesh Journal of Urology, Vol. 20, No. 1, January 2017 p.46-48